Imaging of sacroiliac joints in patients with acromegaly - Ugur, Kader; Karatas, Ahmet; Oz, Burak; Artas, Hakan; Aydin, Suleyman; Koca, Suleyman Serdar (Nature Portfolio, 2019)
Acromegaly can lead to structural alterations of joints and bones. Patients with acromegaly may, therefore, have musculoskeletal complaints. In this study, sacroiliac joints are investigated in patients with acromegaly. 33 patients with acromegaly were enrolled. Sacroiliac joints were examined by X-ray and magnetic resonance imaging (MRI). In acromegaly, sacroiliac joints were abnormal in 36% of the patients by X-ray and 12.1% by MRI. When current axial spondylarthritis (SpA) classification criteria were taken into account, 6.1% of acromegaly patients could be classified as non-radiographic axial SpA and 2% as radiographic axial SpA. Sacroiliac joints are frequently affected in acromegaly and thus this disorder mimics the features of AS and SpA. Acromegaly should be kept in mind in the differential diagnosis of AS and SpA.
Keywords: Society Classification Criteria; Ankylosing-Spondylitis; Clinical-Practice; Spondyloarthritis; Diagnosis; Management